Handbook of Digital 3D Reconstruction of Historical Architecture - Münster, Sander,Apollonio, Fabrizio Ivan,Blümel, Ina,Fallavollita, Federico,Foschi, Riccardo,Grellert, Marc,Ioannides, Marinos,Jahn, Peter Heinrich,Kurdiovsky, Richard,Kuroczyński, Piotr,Lutteroth, Jan-Eric,Messemer, Heike,Schelbert, Georg (Springer Nature Switzerland, Imprint: Springer, 2024)
Zusammenfassung: This open access book is a handbook for students, experts and interested parties who want to learn more about digital 3D reconstruction of historical architecture. The book provides answers to the core questions of the subject: What is a digital 3D model or a digital 3D reconstruction? How are they created and what are they used for? Practical instructions, condensed knowledge, explanations of technical terms and references to example projects, literature and further references provide information of varying density and thus enable an individual introduction to the subject. The book combines extensive knowledge on the topic of
10.1007/978-3-031-43363-4
Keywords: (lcsh)Image processing–Digital techniques.; (lcsh)Computer vision.; (lcsh)Architecture.; (lcsh)Digital humanities.; (lcsh)Archaeology–Methodology.; Computer Imaging; Vision; Pattern Recognition and Graphics.; Architecture.; Digital Humanities.; Archaeological Methods and Modelling.